Pengaruh Kualitas Pelayanan, Kepercayaan, Dan Keamanan Terhadap Kepuasan Konsumen Pengguna Jasa Grabbike Di Kelurahan Kebagusan - Wildan Nuradi Nuradi; Suadi Sapta Putra; Kumba Digdowiseiso (Journal of Economic, Bussines and Accounting (COSTING), 2023)
This study aims to analyze the effect of Service Quality, Trust, and Security on Consumer Satisfaction of GrabBike service users in the Kebagusan Village Area. The data source in this study used primary data in the form of a questionnaire, the research data was given to 100 consumer respondents who used GrabBike services in the Kebagusan Village Area. In taking samples for this study using purposive sampling method. The data analysis technique used is multiple linear regression and hypothesis testing using t-statistics that have been processed from SPSS 25 to test the regression coefficients. Based on the results of the partial study, it was found that Service Quality has a positive and significant effect on Consumer Satisfaction, Trust has a positive and significant effect on Consumer Satisfaction, Security has a positive and significant effect on Consumer Satisfaction. Keywords: Service Quality, Trust, Safety, Customer Satisfaction.